Фотодиод ультрафиолетового диапазона на основе селенида цинка - Perevertailo, V. L.; Dobrovol’skiy, Yu. G.; Popov, V. M.; Pokanevich, A. P.; Matskevich, V. M.; Rizhikov, V. D.; Shabashkevich, B. G.; Yur’yev, V. G. (PE "Politekhperiodika", Book and Journal Publishers, 2010)
The construction and technology of Shottky photodiode on the basis of ZnSe, sensible in the ultraviolet region of spectrum are considered. Researches of electrophysical and photo-electric descriptions of photodiodes of Shottky Nі–ZnSe(Te,O)–Іn are conducted, and it is shown, that they can be applied in devices for radiometry and dissymmetry UV radiations in the ranges UVA, UVB and UVC. Comparison of parameters of developed UV photodiodes based on ZnSe with analogues showed that small capacitance and low value of dark current is their substantial difference of other ones.